Targeting PD-L1 in solid cancer with myeloid cells expressing a CAR-like immune receptor - Myers Chen, Kayla; Grun, Daniel; Gautier, Brian; Venkatesha, Shivaprasad; Maddox, Michael; Zhang, Ai-Hong; Andersen, Peter (Frontiers in Immunology, 2024)
Myeloid cells are prevalent in solid cancers, but they frequently exhibit a pro-tumor phenotype, hindering cancer immunotherapy. Their abundance makes engineered myeloid cell therapy an intriguing approach to tackle challenges posed by solid cancers, such as tumor trafficking and infiltration along with tumor cell heterogenicity and immunosuppressive tumor microenvironment (TME). Solid cancers often upregulate the checkpoint molecule PD-L1 to evade immune responses. Thus, we devised an adoptive cell therapy strategy based on myeloid cells expressing a Chimeric Antigen Receptor (CAR)-like immune receptor (CARIR). The extracellular domain of CARIR is derived from the natural inhibitory receptor PD-1, while the intracellular domain(s) are derived from CD40 and/or CD3x. To assess the efficacy of CARIRengineered myeloid cells, we conducted proof-of-principle experiments using co-culture and flow cytometry-based phagocytosis assays in vitro. Additionally, we employed a fully immunecompetent syngeneic tumor mouse model to evaluate the strategy's effectiveness in vivo. Coculturing CARIR-expressing human monocytic THP-1 cells with PD-L1 + target cells lead to upregulation of the co-stimulatory molecule CD86 along with expression of proinflammatory cytokines TNF-1a and IL-1b. Moreover, CARIR expression significantly enhanced phagocytosis of multiple PD-L1 + human solid tumor cell lines in vitro. Similar outcomes were observed with CARIR-expressing human primary macrophages. In experiments conducted on Balb/c mice bearing aggressive 4T1 mammary tumors, infusing murine myeloid cells expressing a murine version of CARIR significantly slowed tumor growth and prolonged survival. Taken together, our results demonstrate that adoptive transfer of PD-1 CARIR-engineered myeloid cells has the potential to be further developed as an effective strategy in treating PD-L1 + solid tumors.